Physiological and biochemical basis of cold storage in groundnut (Arachis hypogaea L.) seeds: PHYSIOLOGICAL AND BIOCHEMICAL BASIS OF COLD STORAGE IN GROUNDNUT - N NITHYA; J RENUGADEVI (Journal of Oilseeds Research, 2017)
A study to determine the optimumseedmoisture content and storage temperature for groundnut seeds under cold storage conditions in comparison to ambient conditions revealed that the seeds stored at -20ºC with 6 per cent moisture content maintained the seed physiological qualities like germination and vigour index at higher level with minimum loss in biochemical parameters like protein and oil content and less reduction in the activities of dehydrogenase, catalase, peroxidise and lipoxygenase enzymes than the seeds under ambient storage. The supremacy of cold storage was also supported by structural study of seed coat changes through scanning electron microscope and seed health study.